Effects of different methods and time of boron application on the nutrient concentration and uptake by wheat (Triticumaestivum L.) (Bangladesh Journal of Agricultural Research, 2018)
At present, inclusion of Boron (B) in fertilizer management practice most often determines the yield performance of crops. Methods of supply of B to plants demands more research to come to a conclusion. The effect of different methods of boron application on the nutrient concentration and uptake of wheat (Triticuma estivum L.cv. Shatabdi) was studied through a field experiment at Bangladesh Agricultural University (BAU) farm, Mymensingh during rabi season of 2012-13. The experiment was laid out in a randomized complete block design (RCBD) with six treatments and three replications. The treatments were- (i) B–control (no addition of B), (ii) soil application @ 1.5 kg ha-1, (iii) seed priming @ 0.4% boric acid solution, (iv) foliar spray @ 0.4% boric acid solution at primodia stage (37DAS), (v) foliar spray @ 0.4% boric acid solution at booting stage (55 DAS),and (vi) foliar spray at primodia stage (37DAS) and booting stages (55 DAS). Boric acid was used as a source of boron. Seed priming was done by soaking wheat seeds into 0.1% boric acid solution for 10 hours and then seeds were dried before sowing. Foliar spray of B at primodia and booting stage of crop (T6) recorded the highest B concentration of grain (19.60 μg g-1) and the control (T1) treatment performed the lowest B concentration (6.75 μg g-1). Similarly, the foliar spray of B at primodia and booting stages of crop (T6) recorded the highest B uptake by both grain and straw that was statistically identical to foliar spray of B at booting stage of crop (T5) in both cases. In view of cost-return analysis, foliar spray of B at primodia and booting stage treatment required the highest input cost but obtained the highest gross return, while control B required the lowest input cost along with lowest gross returnBangladesh J. Agril. Res. 43(3): 453-469, September 2018